1992
DOI: 10.1002/j.2161-0045.1992.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Career Counseling Is Personal Counseling

Abstract: Despite many changes that have occurred in the field of career counseling, counselors continue to rely on models of counseling that emphasize the rational, informational aspects of career decision making. The author argues that career counselors need to pay more attention to the affective, psychological issues confronting clients with career problems. The impact of significant psychological variables that influence career decision making are discussed: developmental stages and tasks, identity formation and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
21
1
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 24 publications
7
21
1
3
Order By: Relevance
“…Findings of this study are consistent with the findings of previous studies (e.g., Anderson & Niles, 1995;Dorn, 1992;Imbimbo, 1994;Krumboltz, 1993;Manuele-Adkins, 1992) which showed that counseling students hold misconceptions regarding interrelationships between career and personal counseling. Participants with no previous career counseling experience lacked a framework for understanding the purpose or value of career counseling.…”
Section: Discussionsupporting
confidence: 94%
“…Findings of this study are consistent with the findings of previous studies (e.g., Anderson & Niles, 1995;Dorn, 1992;Imbimbo, 1994;Krumboltz, 1993;Manuele-Adkins, 1992) which showed that counseling students hold misconceptions regarding interrelationships between career and personal counseling. Participants with no previous career counseling experience lacked a framework for understanding the purpose or value of career counseling.…”
Section: Discussionsupporting
confidence: 94%
“…This may be true because in recent years career counseling has often been viewed as separate and distinct from personal counseling (Burlew, 1992) and has been reduced to testing and information giving, thereby reducing the richness of the work. Questioning whether a person with a career problem is a case for personal or career counseling ignores a long tradition in the career development field that has consistently recognized the importance of personality factors in the process of finding, choosing, and maintaining a career (Manuele-Adkins, 1992;Patterson, 1964;Super, 1951). Distinguishing between career and personal counseling disregards the reality that individuals have psychological issues that interfere with career exploration and decision making (Bluestein, Devenis, & Kidney, 1989;Hartman, Fuqua, & Blum, 1985;Osipow, Carney, Winer, Yanico, & Koschir, 1976).…”
mentioning
confidence: 99%
“…For example, a client may ask for specific information, an opinion, or aninterpretation of options. The necessity to provide information isrecognised assomething that differentiates career counselling from counselling ingeneral (Gysbers &Moore 1986;Manuele-Adkins, 1992). What is evident in this study isthatall the segments show thatthe counsellor did most ofthe talking.…”
Section: Average Word Countmentioning
confidence: 76%